Pengaruh Beban Kerja, Self Efficacy dan Work Life Balance Terhadap Kepuasan Kerja Pada Badan Pengembangan Sumber Daya Manusia Daerah Provinsi NTB - Nirmala Putri, Andi; Suprayetno, Djoko; Suryatni, Mukmin (Postgraduate, University of Mataram, 2025)
This research aims to analyze the influence of Workload, Self Efficacy and Work Life Balance on Job Satisfaction. The type of research used in this research is associative, namely with a quantitative approach. The data collection method uses a sample with a population of 86 respondents. The data analysis used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, f test and determinant coefficient test. The data analysis technique in this research is the SPSS version 29 program application. The results of this research show the results of statistical analysis, namely: 1) Workload (X1) has a negative and significant effect on Job Satisfaction (Y), 2) Self Efficacy (X2) has a positive and significant effect on Job Satisfaction (Y), 3) Work Life Balance (X3) has a positive and significant effect on Job Satisfaction (Y). So it can be concluded that the lower the workload given, the higher the job satisfaction of employees of the Regional Human Resources Development Agency of NTB Province, then the higher the employee's self-efficacy and good work life balance, the greater the job satisfaction of employees of the Regional Human Resources Development Agency of NTB Province.